The Effect Of Soybean Milk Feeding On Increasing Breast Milk Production In Public Mothers At Nasywa Clinic In 2022 - Joharmi Joharmi; Atika Pohan; Sri Lestari (Institute of Computer Science (IOCS), 2022)
Low milk production is the main problem for new mothers, besides the problem of sinking or flat nipples, swollen breasts, the baby is reluctant to suckle due to improper technique or the baby has a short tongue. The purpose of this study was to determine the effect of giving soy milk (soybean milk) to increasing breast milk production in postpartum mothers at the Nasywa Clinic in 2022. This study used the methodpre-experimental designby designone group pretest-posttest without control. Sampling was done by purposive sampling method. Respondents who were used as samples were 30 postpartum mothers who had problems with insufficient breast milk. The bivariate analysis used in this study was a nonparametric difference test with the Wilcoxon test. The results of this study showed that from 30 respondents, 21 people (70%) complained of not having soy milk before being given the intervention. The increase in breast milk production after being given soy milk was 19 people (63.3%) in the category of smooth breastfeeding and 11 people (36.7%) with non-fluent breast milk. The results of the bivariate analysis showed that there was a significant effect of giving soy milk (soybean milk) to increasing breast milk production in postpartum mothers at the Nasywa Clinic in 2022, with a value of p = 0.002 (p <0.05).